RELATIONSHIP BETWEEN MOTHER'S ATTITUDE AND SOCIO-CULTURE WITH THE INCIDENCE OF LACK NUTRITION IN UNDER-FREE (12-59 MONTHS) - Kamelia ,; Andi Parellangi; Elisa Goretti Sinaga (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Nutrition is crucial for supporting the growth and development of toddlers. The government program aimed at preventing undernutrition is the Supplementary Feeding Program (SFP). The nutritional status can be determined through laboratory tests and anthropometric measurements. The rapid developmental stage of children aged 1-5 years makes them vulnerable to undernutrition if not supported by balanced nutrition. The objective of this study was to examine the relationship between maternal attitudes, socio-cultural factors, and the occurrence of undernutrition in toddlers (12-59 months) in the village of Karangan Seberang. This research employed a descriptive correlational survey design with a cross-sectional approach. The total population of toddlers aged 12-59 months was 100 individuals, with a sample size of 86. The sampling technique used was accidental sampling. The univariate analysis revealed that 31 (36%) respondents experienced undernutrition, while 55 (64.0%) respondents did not. The bivariate analysis using the chi-square test showed a p-value of 0.000 < α value of 0.05, indicating a significant relationship between maternal attitudes, parental education, economic factors, and parental knowledge with undernutrition in toddlers (12-59 months) in the village of Karangan Seberang. There is a significant relationship between maternal attitudes, parental education, economic factors, and parental knowledge with undernutrition in toddlers (12-59 months) in the village of Karangan Seberang. Close collaboration among the government, healthcare institutions, education sector, and the community is needed to address the issue of undernutrition in children. Effective coordination and synergy between these sectors can help enhance awareness, knowledge, and effective actions in combating undernutrition.